Developmental research methods - Miller, Scott A. 1944- (SAGE, 2018)
"The Fifth Edition of the classic Developmental Research Methods presents an overview of methods to prepare students to carry out, report on, and evaluate research on human development across the lifespan. The book explores every step in the research process, from the initial concept to the final written product, covering conceptual issues of experimental design, as well as the procedural skills necessary to translate design into research. Incorporating new topics, pedagogy, and references, this edition conveys an appreciation of the issues that must be addressed, the decisions that must be made, and the obstacles that must be overcome at every phase in a research project, capturing both the excitement and the challenge of doing quality research on topics that matter."--back cover.